Penentuan Harga Pokok Produksi Sebagai Dasar Penentuan Harga Jual Gula Merah Di Desa Bukti - Indrawati, Luh Sri; Dewi, Ni Wayan Yulianita (Jurnal Ilmiah Akuntansi dan Humanika, 2022)
The purpose of this study is 1) to determine the cost of brown sugar production which has been practiced by brown sugar producers in Bukti Village. 2) To determine the calculation of the cost of brown sugar production in The Evidence Village based on the full costing method. 3) To find out the comparison of the determination of the cost of goods produced by brown sugar that has been practiced by producers with the determination of the cost of goods produced in accordance with the full costing method. This research uses qualitative research methods. Data collection was carried out by methods of 1) observation during the implementation of the Brown Sugar manufacturing process in the business, 2) interviews with employees and brown sugar business owners in Bukti Village, 3) documentation studies by analyzing the costs incurred during the brown sugar production process. The data analysis techniques used are miles and Humberman's model. The results of this study show that in determining the cost of goods produced in the brown sugar business in Bukti Village, it has not included factory overhead costs as a component of production costs, the determination of the cost of goods produced in the brown sugar business in Bukti Village is still carried out simply, but using the full costing method can have a significant effect on the sustainability of the brown sugar business in Bukti Village.